The Impacts of the Project-Based Learning and Problem-Based Learning Models with Self-Confidence on Students’ Learning Outcomes - Safitri, Rahmita; Alnedral; Gusril; Wahyuri, Asep Sujana; Ockta, Yovhandra (Indonesian Research Journal in Education |IRJE|, 2024)
This research explored the impact of Project-Based Learning (PjBL), Problem-Based Learning (PBL), and Self-Confidence on the learning outcomes of short-distance running of athletics in Sports Education. It emphasized that quality learning depends on effective design, adequate facilities, and teacher creativity. The research method involved a quasi-experimental design, testing the influence of PjBL, PBL, and self-confidence on student learning outcomes. The results indicated significant differences in learning achievements based on the applied models. The PjBL and PBL models individually impacted on learning outcomes, with students exhibiting higher engagement and understanding. However, the combination of all three factors did not show a significant influence on learning outcomes. In conclusion, the research suggests that adopting innovative learning models, such as PjBL and PBL, along with fostering students' self-confidence, can enhance the learning experience in sports education.